A Novel Insight Into Fecal Occult Blood Test for the Management of Gastric Cancer: Complication, Survival, and Chemotherapy Benefit After R0 Resection - Lu, Jun; Xu, Binbin; Xu, Yu; Wu, Yuan; Xie, Jianwei; Wang, Jiabin; Lin, Jianxian; Chen, Qiyue; Cao, Longlong; Zheng, Chaohui; Huang, Changming; Li, Ping (Frontiers in Oncology, 2021)
Background: Previous studies have shown that the all-cause mortality and non-colorectal cancer mortality of patients with fecal occult blood test (FOBT) positivity are significantly increased, implying that FOBT results may have more prognostic value. Methods: Retrospective analysis was performed for gastric cancer (GC) patients who underwent R0 gastrectomy from July 2007 to July 2014 at our hospital. Propensity score matching (PSM) was used to reduce confounding bias and a computerized technique for the nearest available score matching without replacement was applied. The cumulative survival rate was calculated using the Kaplan-Meier method and a log-rank test. Cox proportional hazards regression and logistic regression was used to determine the independent prognostic factors associated with survival and postoperative complications, respectively. The expression level of tumor-associated macrophages (TAMs) and proinflammatory cytokines (TNF-α, IL-6) were evaluated by immunohistochemical (IHC). Results: A total of 3003 patients were included and 246 patients (8.2%) were in preoperative FOBT positive status. There was no significant difference in demographic data between preoperative FOBT positive and negative group after a 1:4 PSM. The overall postoperative complications, major complications and anastomotic leakage were significantly higher in the preoperative FOBT-positive group than in the preoperative FOBT -negative group. Moreover, preoperative FOBT-positivity was an independent risk factor for 5-year overall survival (OS) (HR: 1.32, p=0.005). For stage II/III patients, the postoperative adjuvant chemotherapy (PAC) benefit was found in preoperative FOBT-negative group (5-year OS: 49.9% vs. 36.8%, p=0.001), whereas the PAC benefit was lost in preoperative FOBT -positive groups (5-year OS: 40.8% vs. 37.7% p=0.896). Finally, IHC found that preoperative FOBT-positivity in patients was significantly associated with higher TAMs infiltration and higher expression of IL-6 and TNF-α in tumor tissues than in the preoperative FOBT-negative group. Conclusion: As a simple and low-cost method, preoperative FOBT results can predict both complications and survival after R0 gastrectomy for GC. More importantly, stage II/III GC patients with FOBT-positive seem not benefit from PAC alone. Further exploration is warranted.